Short-term effects of temperature and air pollution on mortality in Norway: a nationwide cohort-based study - Rao, Shilpa; Zhang, Siqi; Ahimbisibwe, Ashley; Bekkevold, Terese; Di Ruscio, Francesco; Diz-Lois Palomares, Alfonso; Frohn, Lise Marie; Geels, Camilla; Vázquez Fernández, Liliana; Schneider, Alexandra (Frontiers in Environmental Health, 2024)
Background: This time-stratified case-crossover study examined short-term associations of air temperature with cause-specific mortality (natural-cause, cardiovascular and respiratory) and potential effect modification by daily mean air pollution concentrations and individual characteristics in the Cohort of Norway (CONOR) cohort. Methods: The CONOR cohort recruited ~173,000 participants from 1994 to 2003. Participants’ vital status and the cause of death were collected from the Cause of Death Registry of Norway until 2018. Daily mean air temperatures and concentrations of fine particulate matter (PM2.5) and ozone (O3) estimated by spatial-temporal models were assigned to participants’ residences. We applied conditional logistic regression models with the distributed lag non-linear model approach to assess cold and heat effects on cause-specific mortality. The potential effect modification was analyzed by incorporating an interaction term between air temperature and the modifier in the regression model. The cold and heat effects were estimated for different subgroups of participants and at the low (5th percentile), medium (50th percentile), and high (95th percentile) levels of air pollution. Results: During the follow-up period, we identified 40,040 cases of natural-cause deaths, including 14,457 and 3,699 cases of deaths from cardiovascular and respiratory diseases, respectively. We observed an increased risk of natural-cause mortality (OR: 1.26 95% CI: 1.09, 1.46) for a decrease in temperature from the minimum mortality temperature (MMT, 17.6 °C) to the 1st percentile and an increased risk of cardiovascular mortality (OR: 1.32, 95% CI: 1.04, 1.67) for a decrease from MMT (16.1 °C) to the 1st percentile. The cold effect on natural-cause mortality was more pronounced among women, former smokers, those aged below 75 years and people with a history of cardiovascular diseases. The cold effect on natural-cause mortality was stronger at higher levels of air pollution in winter, and the heat effect on cardiovascular mortality were stronger with elevated air pollution levels in summer. Conclusion: Our findings provide evidence for adverse short-term cold effects and the additional impacts of air pollution on mortality. We identified sub-populations who were likely to be more at risk of temperature-related mortality. These results are significant in developing climate adaptation strategies in Norway.